THE WORK PROCESS OF NURSES IN HOSPITAL EPIDEMIOLOGY CENTERS - Adeli Regina Prizybicien de Medeiros; Liliana Müller Larocca; Maria Marta Nolasco Chaves; Aida Maris Peres (Universidade Federal do Paraná, 2015)
This exploratory and qualitative study aimed to characterize the work process of nurses from Hospital Epidemiology Centers in relation to the agents, aim, means and instruments, object and products. The data were collected between March and May 2012, through open interviews held with nine nurses from five Hospital Epidemiology Centers in the city of Curitiba, Paraná, in accordance with Resolution 196/96. The study made it possible to identify the constituent elements of the work of the nurse in Hospital Epidemiological Surveillance and evidenced practices which are still incipient in some institutions. It emerged that the professional practice, in the centers referred to, must break from the task-centered model of work, in favor of a model which is articulated with specialist services and which contributes to the construction of Public Policies aligned with the population's health needs.